An Impact of Capital Adequacy Ratio on the Profitability of Private Sector Banks in India – A Study - Jayesh J Jadhav; Ashish Kathale; Shreeya Rajpurohit (International Journal of Engineering and Management Research, 2021)
Profitability being one of the cardinal principles of bank lending acts as a game changer for the survival and success of private sector banks in India. In order to stay profitable, banks have to capitalise on every penny advanced to yield the expected returns. However, considering the constraints laid down by the Reserve Bank of India, banks have to maintain a minimum capital adequacy ratio, as per the current BASEL III regulations active in India. With the mergers of public sector banks, the challenge has got just tougher for the private sector banks in India. Expansion and Diversification are the key strategies adopted by the key players from the private banking sector, however, with the minimum capital adequacy ratio observed by them, it is necessary to understand its actual impact on the bank’s profitability. This research paper aims to throw light upon the linkage that capital adequacy has with the bank’s profitability. It attempts to establish a relation between the Capital Adequacy Ratio with the Net profits of the bank. For the purpose of this study, data from the past 5 years of the leading private sector banks has been collected, namely, HDFC Bank, ICICI Bank, Kotak Mahindra Bank, AXIS Bank and YES Bank. The collected data has been analysed using Pearson’s Correlation to establish a relation between the CAR Ratio & the bank’s profitability. Hypothesis testing has been further done to study the quantum of proportionate change in the profitability with a change in the CAR Ratio for private sector banks using applicable research tools. The said research tools are applied to achieve the desired results while maintaining the required quantum of accuracy. It also aims to understand the proportionate impact of changes in CAR to the bank’s profitability, which can act as a suggested measure for banks to develop a reliable framework for efficient capital management and increase overall efficiency. The results derived from the data collected and analyzed aim to provide scope for further study on the subject matter.